A METHODOLOGICAL APPROACH TO THE CHARACTERIZATION OF BRAIN GLIOMAS, BY MEANS OF SEMI-AUTOMATIC MORPHOMETRIC ANALYSIS - Surowka, Artur Dawid; Adamek, Dariusz; Radwanska, Edyta; Lankosz, Marek; Szczerbowska-Boruchowska, Magdalena (Image Analysis and Stereology, 2014)
The aims of this paper were to present a reliable morphometric procedure for glioma analysis for preliminary prognosis and to develop a semi-automatic procedure that is easy to use. The data presented are important to the extent that they verify the reliability of the results by showing that they are consistent with the findings from more complicated automatic analytical tools. The objects for analysis were digital images of haematoxylin-eosin stained glioma samples. The overall analysis consisted of digital image analysis and the determination of morphometric parameters. Interestingly, an increase in the mean values of aspect ratio with increasing malignancy grade was found. Moreover, the morphometric parameters in relation to the histological origin of gliomas were examined and it was found that, the cellular nuclei of glioblastoma multiforme reveal the biggest mean values of aspect ratio compared with other gliomas.